Mnemonics of World War II in Pomerania, Traumatic War Events in Regional Memory Transmissions - Kozyczkowski, Krzysztof (My University, 2017)
Within this study I investigate the importance of traumatic war memories in the contemporary social memory of the Pomerania region. Thus the research topic focuses predominantly on memory studies, history and ethnography. The goal of research is to analyze how traumatic memories of World War II are commemorated in the region of Pomerania. Why certain events are commemorated with more detail while others fade, and become forgotten. How are those processes influenced? It can be argued that memory is the source of our identification capabilities, as how would we define “us” from “them” with no recollection of the past. The primary material for this work comes from two forms of interviews. Interviews that come from publications, that represent the memories of people who survived the war. And interviews that have been gathered by the researcher, and represent the memory narratives/perceptions existing in the 3rd generation after the war. Thus the research data is dominantly qualitative. To examine the materials I have used a thematic analysis of the interviews coming from publications, this was performed to track down the most often appearing memories of traumatic events. For the 3rd generation interviews a narrative analysis was used to find the patterns and differences, that exist in narratives related to memories of traumatic war events. Through the analysis I have come to the conclusion, that commemoration of events is not only highly dependent on the state narrative, but is also affected by regional narratives existing in the social memory. Memories even the most traumatic ones, become an important aspect of regional identity, and the memorization of such events from a regional perspective allows to build a form of defensive wall, that would at the very least slow down the domination of state created memories, in this way allowing the perception of regional “us”, to exist alongside the state formed identity. Thus the research shows the importance of regional historians, who explore the past of specific regions, a past that usually ends up outside of the national narrative, and as such is set aside unexplored, or unexplained.